Design of an FPGA-Based High-Speed Data Acquisition System for Frequency Scanning Interferometry Long-Range Measurement - Sivagunalan Sivanathan; Mohammed Ali Roula; Kang Li; Dun Qiao; Nigel Joseph Copner (IEEE Open Journal of Instrumentation and Measurement)
Frequency scanning interferometry (FSI) has become a popular method for long-range, targetbased, distance measurements. However, the cost of developing such systems, particularly the electronic components required for high-speed data acquisition (DAQ), remains a significant concern. In this article, we present a cost-effective, FPGA-based real-time DAQ system specifically designed for FSI, with a focus on long absolute distance measurements. Our design minimizes the use of third-party intellectual property (IP) and is fully compatible with the Xilinx FPGA 7 series families. The hardware employs a 160-MS/s, 16-bit dual-channel ADC interfaced to the FPGA via a low-voltage differential signaling (LVDS). The proposed system incorporates an external sampling clock, referred to as the K-clock, which linearizes the laser’s tuning rate, enabling optical measurements to be sampled at equal optical frequency intervals rather than equal time intervals. Additionally, we present the design of a high-speed, 160-MS/s ADC module for the front-end analog signal interface and the LVDS connection to the chosen FPGA. We demonstrate that the digitized data samples can be efficiently transmitted to a polarization controller (PC) application via a USB interface for further processing.